Pola Sebaran Rotan (Calamus spp.) di Hutan Lindung Desa Sassa Kabupaten Luwu Utara - Witno Witno; Maria Maria; Forestri Cimbrins (Fakultas Kehutanan Universitas Gadjah Mada, 2022)
The Sassa Village Protection Forest has several rattan types in several forest areas. As a plant belonging to the Arecaceae tribe, rattan has a distribution pattern that varies according to where it grows. The distribution pattern describes the distribution of individuals in a population, such as clustered, random or regular patterns. This study aimed to determine the distribution pattern of rattan in the Protected Forest of Sassa Village, Baebunta District. Data was collected by placing plots using purposive sampling with technical data analysis in the form of density and frequency of rattan species and distribution patterns using the Morishita index. The results of this study obtained two distribution patterns of rattan based on the type, namely the uniform distribution pattern found in the kind of rattan Lambang (Calamus ornatus Blume), Pahit rattan (Calamus usitatus Blanco), Susu rattan (Daemonorop robusta Warb). The clumped distribution pattern consists of Jermasin rattan (Calamus ecojolis Becc), Saloso rattan (Calamus sp.) Tohiti rattan (Calamus inops Beccari).